1973
DOI: 10.1093/cvr/7.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the relationship between the catecholamine distribution in the atrium and the specific granules present in atrial muscle cells: 1. Isolation of a purified specific granule subfraction

Abstract: AUTHORS' SYNOPSIS Electron microscopy of mammalian atrial muscle cells reveals a population of speciJic granules suggesting that the atrial muscle cells may have a secretory function. As a preliminary step towards the investigation of the function of the specific granules, a procedure was designed to isolate these particles by differential and density gradient centrifugation of rat atrial homogenates. The specific granule preparation obtained showed a considerable degree of purification with respect to marker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The granules were similar to those found in other organs that secrete peptide hormones [13,14]. The first hint that ANP secretion might be physiologically regulated was observed by De Bold [15] who showed that atrial granularity decreased significantly in rats on 2% NaCl plus mineralocorticoids while granularity increased in both water restricted or NaCl restricted rats.…”
Section: Atrial Distensionsupporting
confidence: 76%
“…The granules were similar to those found in other organs that secrete peptide hormones [13,14]. The first hint that ANP secretion might be physiologically regulated was observed by De Bold [15] who showed that atrial granularity decreased significantly in rats on 2% NaCl plus mineralocorticoids while granularity increased in both water restricted or NaCl restricted rats.…”
Section: Atrial Distensionsupporting
confidence: 76%
“…The heavier ANF peak probably represent mature granules (49), whereas the lighter fraction, which sediments in the region of the Golgi marker galactosyl transferase, probably represents ANF immunoreactivity associated with Golgi complex components. However, the highest purification of G o ␣ took place in a region of the gradient that is of lighter density than either the Golgi marker or ANF, thus suggesting that the association between ANF and G o ␣ is not quantitatively as important as the association of G o ␣ with lower density subcellular elements.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of salt, when BP values are low, it is clear that the renin-angiotensin-aldosterone and sympathetic nervous systems are key for restoring homeostasis. 108 With volume expansion, natriuretic peptides initially described by de Bold and Bencosme 109,110 also have been proposed as important for maintenance of BP. Although several important hormonal and cytokine systems have been implicated and intensively studied by laboratories across the world, 111,112 we will focus this review on another factor, collectively referred to as the cardiotonic steroids (CTS; also called endogenous digitalis-like substances), 113 which are emerging as a class of hormones mechanistically linked to natriuresis.…”
Section: Molecular Physiological and Pathophysiological Studiesmentioning
confidence: 99%